Induced T regulatory cells suppress osteoclastogenesis and bone erosion in collagen-induced arthritis better than natural T regulatory cells. Issue 9 (4th July 2012) - Kong, Ning; Lan, Qin; Chen, Maogen; Zheng, Tina; Su, Wenru; Wang, Julie; Yang, Ziyan; Park, Ryan; Dagliyan, Grant; Conti, Peter S; Brand, David; Liu, Zhongmin; et al.
Abstract : Background: Although natural regulatory T cells (nTregs) can suppress osteoclastogenesis, the role of TGF-β-induced CD4+Foxp3+ Tregs (iTregs) in osteoclastogenesis remains unknown. Objective: To determine the effects of iTregs on osteoclastogenesis in vitro and on bone erosion in vivo in collagen-induced arthritis (CIA). Methods: Osteoclastogenesis was induced in bone marrow CD11b+ cells with receptor activator of nuclear factor κ B (NF-κB) ligand (RANKL) and macrophage colony stimulating factor. Graded doses of Tregs were added to inhibit osteoclastogenesis. Transwell and antibody blockade experiments were performed to assess the roles for cell contact and soluble cytokines. NF-κB activation was determined by western blot. iTregs or nTregs were adoptively transferred to mice with CIA to assess in vivo effects on disease incidence and bone erosion, the latter determined by CT scanning. Results: Both nTregs and iTregs greatly suppressed osteoclastogenesis in vitro, but only iTregs sustained this effect when interleukin-6 was present. iTregs, but not nTregs, significantly suppressed development of CIA. Bone erosions in iTregs-treated mice were diminished compared with untreated mice or nTregs-treated mice. Treatment with iTregs, but not with nTregs, dramatically decreased NF-κB p65/p50 levels in osteoclasts in vitro and p65/50 and RANKL expression by synovial tissues in vivo. Conclusion: iTregs may be therapeutically beneficial in rheumatoid arthritis and related diseases associated with bone erosions.